ANALISIS KETERSEDIAAN APLIKASI WISATA HALAL BERBASIS ANDROID TERHADAP JUMLAH KUNJUNGAN WISATA DI PRINGSEWU - Dewi, Nirmala (STMIK Pringsewu, 2025)
This study aims to analyze the influence of the availability of Android-based halal tourism applications on the number of tourist visits in Pringsewu Regency using a quantitative approach. Data were collected through the distribution of questionnaires to tourists and analysis of tourism visit data from relevant agencies. The data analysis technique used is simple linear regression. The results of the study indicate that the availability of halal tourism applications has a positive and significant effect on the increase in tourist visits. These findings suggest that the use of digital technology, particularly mobile applications, can be an effective strategy in supporting the development of halal tourism in the region. The application provides information about halal tourist attractions along with relevant details. It also features an integrated map that helps tourists find routes to their destinations through Google Maps using GPS navigation.